Inequalities in health between First Nations adults living off-reserve and non-Indigenous adults in Canada - Hu, Min; Hajizadeh, Mohammad; Bombay, Amy (My University, 2024)
This study investigates health inequalities between non-Indigenous and First Nations adults living off-reserve in Canada using data from the 2017 Aboriginal Peoples Survey and the 2017 Canadian Community Health Survey. The researchers found that observable characteristics account for 20 to 45 percent of disparities in general health, mental health, and diabetes. Socio-economic factors, including employment, income, and education, explain 10 to 25 percent of these differences. The findings suggest that improving socio-economic conditions could significantly reduce health disparities between First Nations and non-Indigenous populations, addressing a crucial aspect of health equity.
Keywords: Health; Indigenous peoples